The Time is Now: An Overview on Perinatal Psychiatry - Rema, João Paulo (2022)
Perinatal mental health (PMH) has been a growing field of practice for psychiatry in the last decades. It focuses on mental health during pregnancy, childbirth and the postpartum period including the distinctive presentations of mental illness and well‐being challenges associated with parenting experiences. Mental health problems in pregnancy and the postnatal period can have significant differences and challenges to its approach compared to other periods of life. Working in PMH requires specific and updated know ‐ledge regarding carers’ experiences and manifestations of mental illness in this particular life stage and psychotropic management during pregnancy and breastfeeding, as well as regarding the mother/parent and baby relationship and bond, and the baby’s safeguarding along several developmental issues. For all this, PMH specialist services and multidisciplinary teams with specific training have been developing to cater to this need in several countries around the world. To provide a broadened overlook on the matter, some key aspects of PMH will be discussed below in this perspective.